The Impact of Gender Equality and Inclusive Leadership Programs on Students - Nurhikmah Nurhikmah; Tusiana Dewi; Nadila .; Rizki Ade Purnamasari; Uswatun Hasanah; Fauzi Juliannnor (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2026)
This Community Service initiative was designed to strengthen students' conceptual understanding and practical engagement with gender equality and inclusive leadership within higher education institutions. The program was conducted on October 31, 2025, at the STIMI Banjarmasin auditorium, located on Jalan Kuripan No. 26, Banjarmasin. It was developed as a research-based intervention addressing previously identified gaps between academic motivation and inclusive organizational practices among student leaders at STIMI Banjarmasin. A Participatory Action Research (PAR) approach grounded in Reflective Teaching and Learning (RTL) was implemented, involving 32 student organization members. Program effectiveness was evaluated through structured pre-test and post-test assessments combined with qualitative reflection analysis. Findings demonstrate a 32.5% increase in gender equality understanding and a 28.1% increase in inclusive leadership attitudes. Participants also generated concrete organizational action plans aimed at promoting equitable participation and gender-responsive governance. These results indicate that participatory and reflective community engagement can function as an institutional mechanism for embedding inclusive leadership culture in higher education.This Community Service initiative was designed to strengthen students' conceptual understanding and practical engagement with gender equality and inclusive leadership within higher education institutions. The program was conducted on October 31, 2025, at the STIMI Banjarmasin auditorium, located on Jalan Kuripan No. 26, Banjarmasin. It was developed as a research-based intervention addressing previously identified gaps between academic motivation and inclusive organizational practices among student leaders at STIMI Banjarmasin. A Participatory Action Research (PAR) approach grounded in Reflective Teaching and Learning (RTL) was implemented, involving 32 student organization members. Program effectiveness was evaluated through structured pre-test and post-test assessments combined with qualitative reflection analysis. Findings demonstrate a 32.5% increase in gender equality understanding and a 28.1% increase in inclusive leadership attitudes. Participants also generated concrete organizational action plans aimed at promoting equitable participation and gender-responsive governance. These results indicate that participatory and reflective community engagement can function as an institutional mechanism for embedding inclusive leadership culture in higher education.